2017
DOI: 10.1038/s41537-017-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Learning stable and predictive network-based patterns of schizophrenia and its clinical symptoms

Abstract: Schizophrenia is often associated with disrupted brain connectivity. However, identifying specific neuroimaging-based patterns pathognomonic for schizophrenia and related symptom severity remains a challenging open problem requiring large-scale datadriven analyses emphasizing not only statistical significance but also stability across multiple datasets, contexts and cohorts. Accurate prediction on previously unseen subjects, or generalization, is also essential for any useful biomarker of schizophrenia. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
(89 reference statements)
2
28
0
Order By: Relevance
“…The emerging literature has also shown that AI is proving to be useful in these clinical areas. For example, researchers built a predictive model based on machine learning using whole-brain functional magnetic resonance imaging (fMRI) to achieve 74% accuracy in identifying patients with more severe negative and positive symptoms in schizophrenia, suggesting the use of brain imaging to predict the disease and its symptom severity 20. In another study, researchers demonstrated that a linguistic machine learning system, using fMRI and proton magnetic resonance spectroscopy ( 1 H-MRS) inputs, showed nearly perfect classification accuracy and was able to predict lithium response in bipolar patients with at least 88% accuracy in training and 80% accuracy in validation, allowing psychiatrists the ability to predict lithium response and avoid unnecessary treatment 21…”
Section: Resultsmentioning
confidence: 99%
“…The emerging literature has also shown that AI is proving to be useful in these clinical areas. For example, researchers built a predictive model based on machine learning using whole-brain functional magnetic resonance imaging (fMRI) to achieve 74% accuracy in identifying patients with more severe negative and positive symptoms in schizophrenia, suggesting the use of brain imaging to predict the disease and its symptom severity 20. In another study, researchers demonstrated that a linguistic machine learning system, using fMRI and proton magnetic resonance spectroscopy ( 1 H-MRS) inputs, showed nearly perfect classification accuracy and was able to predict lithium response in bipolar patients with at least 88% accuracy in training and 80% accuracy in validation, allowing psychiatrists the ability to predict lithium response and avoid unnecessary treatment 21…”
Section: Resultsmentioning
confidence: 99%
“…Given the role of environment, it is unlikely to find a genetic test that predicts with 100% certainty the individuals who will develop SCZ solely based on genomic data. If, however, such a predictive algorithm is trained using genomic data (including both exonic mutations and CNVs), transcriptome data, and ML approaches using other phenotypic information, such as speech (Bedi et al, 2015) or neuroimaging data (Gheiratmand et al, 2017) are available in study phs000473.v1.p1. We thank the authors and dbGaP for access to the WES data.…”
Section: Limitationsmentioning
confidence: 99%
“…These connectivities were calculated as in § § 2.3 and 4.1. More sophisticated choices of Regions Of Interests and functional-connectivity measures (Marrelec and Fransson, 2011;Smith et al, 2011;Wang et al, 2014;Gheiratmand et al, 2017;Demirci et al, 2008) or even integration of functional and structural imaging (Michael et al, 2010) could obviously lead to an increased predictive power. A different choice of sufficient statistics could also improve the performance.…”
Section: Possible Improvementsmentioning
confidence: 99%